The Rights of Non-Muslims in an Islamic State: A Literature Review - Muchtar, Ayi Ishak Sholih (Research and Development Institution, Darussalam Institute for Islamic Studies, 2022)
This study aims to elaborate on the concept of Islamic teachings on the rights of non-Muslims in an Islamic country. This study uses the literature study method, which is a data collection method directed at searching for data and information through scientific articles and scientific books, both in scientific journals, scientific forum proceedings, and scientific research reports. The results of the study show that non-Muslims who live among Muslims (ahlu al-dzimmah) receive protection, have equal rights and obligations, and obtain an equal position with Muslims. Muslims, especially Muslim leaders, have an obligation to provide protection to non-Muslims. Islamic leaders have an obligation to provide legal instruments and legislation, which guarantee the basic rights of non-Muslims, and obtain equality before the law.